PERTIMBANGAN WISATAWAN MELAKUKAN MAKAN MALAM DI LUAR HOTEL (DINING OUT) - Ngurah Budiasa, I Gusti Putu (Pusat penelitian & Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2011)
Food and beverage revenue is the second major income for the hotel business and guests in the house as the main target market for restaurants and bars inside the hotel. Data from some hotels in Nusa Dua resort area show that most of their guests have dinner outside the hotel. The purpose of this study was to find out reasons or motivationof the hotels guests to have dinner outside the hotel or to dine out. Data were collected by self administered questionnaire by guests who stayed in Nusa Dua area and were analyzed using factor analysis. The result shows that there were three main reasons why guests had dinner outside the hotel or dining out namely to get a good value for money, to relax in a good atmosphere, and to know the surrounding area.